2017
DOI: 10.1681/asn.2017040371
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Renal GLUT2 by the Cannabinoid-1 Receptor: Implications for the Treatment of Diabetic Nephropathy

Abstract: Altered glucose reabsorption the facilitative glucose transporter 2 (GLUT2) during diabetes may lead to renal proximal tubule cell (RPTC) injury, inflammation, and interstitial fibrosis. These pathologies are also triggered by activating the cannabinoid-1 receptor (CBR), which contributes to the development of diabetic nephropathy (DN). However, the link between CBR and GLUT2 remains to be determined. Here, we show that chronic peripheral CBR blockade or genetically inactivating CBRs in the RPTCs ameliorated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 54 publications
(81 reference statements)
9
66
1
Order By: Relevance
“…Inhibition or deletion of CB1R also reduced glucose transporter 2 overexpression and translocation to the brush border membrane of proximal tubular epithelial cells, strongly suggesting that CB1R can contribute to tubulointerstitial fibrosis by enhancing tubular glucose reabsorption during hyperglycemia. 27 Data from human kidney biopsies confirm the CB1R and CB2R imbalance reported in experimental diabetes. 16,25 Although there is no evidence supporting a causal relationship between ECS deregulation and DKD in humans, except for an association between DKD and a CB1R polymorphism, 28 these preclinical data, showing efficacy of drugs devoid of central effects even after albuminuria onset, have opened the way to a novel area of research with potential clinical impact in humans.…”
Section: Cb1 Oxidative Stresssupporting
confidence: 56%
“…Inhibition or deletion of CB1R also reduced glucose transporter 2 overexpression and translocation to the brush border membrane of proximal tubular epithelial cells, strongly suggesting that CB1R can contribute to tubulointerstitial fibrosis by enhancing tubular glucose reabsorption during hyperglycemia. 27 Data from human kidney biopsies confirm the CB1R and CB2R imbalance reported in experimental diabetes. 16,25 Although there is no evidence supporting a causal relationship between ECS deregulation and DKD in humans, except for an association between DKD and a CB1R polymorphism, 28 these preclinical data, showing efficacy of drugs devoid of central effects even after albuminuria onset, have opened the way to a novel area of research with potential clinical impact in humans.…”
Section: Cb1 Oxidative Stresssupporting
confidence: 56%
“…Blood glucose and glycated haemoglobin levels were similar in untreated and treated DM, showing dissociation of albuminuria from hyperglycaemia, the former being reversed and the latter remaining unaffected by dual treatment. Although CB 1 receptor blockade has been reported to modestly ameliorate hyperglycaemia in mice with type 1 diabetes by reducing tubular glucose re-adsorption and thus glycosuria (Hinden et al, 2017), this was not observed in our AM6545treated mice. Treatment with perindopril significantly lowered BP levels, providing evidence of perindopril efficacy, although angiotensin levels were not directly measured.…”
Section: Figurecontrasting
confidence: 72%
“…Considering CB1 participation, its activation was shown to decrease insulin signaling, reduce proliferation and viability of pancreatic ÎČ-cells, and to promote pancreatic inflammation [228,229]. CB1 antagonists (e.g., JD5037-3 mg/kg) were shown to reverse diabetic neuropathy (DN) in mice via modulation of glucose transporter 2 (GLUT-2) expression and activity in renal proximal tubule cells [230,231]. Furthermore, AM6545 (10 mg/kg/day), a peripheral CB1 antagonist, combined with angiotensin-converting enzyme (ACE) inhibitor, was shown to reverse albuminuria, nephrin loss, and to inhibit inflammation in rodent model of DN [232].…”
Section: Diabetesmentioning
confidence: 99%